2011
DOI: 10.1111/j.1365-2621.2011.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Slovenian honeys on the basis of sensory and physicochemical analysis with a chemometric approach

Abstract: The purpose of this study was sensory and physicochemical characterisation of Slovenian honeys with a chemometric approach. Honey samples were obtained from the beekeepers in different natural geographical macroregions of Slovenia. The sensory characteristics of the seven main types of Slovenian honeys are described, together with the physicochemical analyses. The average results of electrical conductivity (0.19-1.61 mS cm )1 ), pH (4.01-5.51), free acidity (13.3-30.9 meq kg )1 ), proline content (317-558 mg k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
5
28
0
2
Order By: Relevance
“…For the acacia and linden honeys in the present study, L* and a* values were generally similar to those reported by Bertoncelj et al (2011), but b* was much lower. They showed that the b* value of Bertoncelj et al (2011).…”
Section: Discussion Colour Parameters Of Fresh Honeyssupporting
confidence: 90%
“…For the acacia and linden honeys in the present study, L* and a* values were generally similar to those reported by Bertoncelj et al (2011), but b* was much lower. They showed that the b* value of Bertoncelj et al (2011).…”
Section: Discussion Colour Parameters Of Fresh Honeyssupporting
confidence: 90%
“…17 Analytical methods have been combined with chemometrics. Multivariate analysis using common tests (FRAP, ABTS, DPPH, color, pH, and flavonoid content) has been found to be an efficient method for differentiation of eucalyptus, "morrão de candeia," and "cambara" honeys.…”
Section: Chemometricsmentioning
confidence: 99%
“…Moreover, the negative correlation between the organoleptic perception of chestnut or eucalyptus and the parameters L * and b * showed that, the darker the blends were, the more they tasted like chestnut or eucalyptus and the less like thyme honey. Indeed, the darker honeys usually have a higher electrical conductivity than the lighter ones, although this is not a rule . Anupama et al .…”
Section: Discussionmentioning
confidence: 99%